SOLUSI PENGEMBANGAN UMKM MELALUI ONTOLOGI - Susanto, Irwan (Performance, 2016)
SMEs proved as the most contributor (92.71%) to the Indonesian employment. Ironically SMEs have many problems. Several attempts were employed, but they were unsucceessful. This article reached the problem solution through onthological philosophy as the novelty. Through descriptive analysis, SMEs were viewed from four dimensions (quantity, autonomy-correlation, dynamic of the process, meaning-value). The result of the study of onthology that described the reality of SMEs Indonesian context is the con-cept of businesses activities which cannot stand alone. It must correlate with the govern-ment and the environment and society and proceed dynamically to adjust to the environ-ment that is formed from the value of the nation's character (togetherness, brotherhood, mutual cooperation). The implications of onthology are the concept of SME development that should be based on the character of SMEs. SMEs still need protection and proactive support on both micro-businesses and macro-businesses aspect of SMEs, by all stake-holders such as government, business associations, universities. To make SMEs grow, it needs government’s integrated policies that can encourage the development of SMEs.